The proposition of factors for analysis of the maintenance of agricultural tractors from a systematic bibliographic review - Silveira, Franco da; Machado, Filipe Molinar; Amaral, Fernando Gonçalves; Santos, Bruno Miranda dos; Rodrigues, Paulo Cesar Chagas (Revista Gestão da Produção Operações e Sistemas, 2020)
The maintenance of agricultural tractors can be understood as the set of procedures that seek to keep the equipment in the best working conditions. However, carrying out adequate planning that can help optimize the maintenance of agricultural tractors is a complex task. The article consists of identifying and presenting a proposal of analysis factors for the maintenance of agricultural tractors, as well as their technical characteristics and modes of operation. In methodological terms, a Systematic Bibliographic Review was applied on maintenance and planning for agricultural tractors in two international databases. The research is classified as descriptive and comparative, of an exploratory nature. As a result, the study contributed to the information gap regarding the maintenance of agricultural tractors. In addition, we identified the main factors that must be analyzed to keep the equipment in the best operating conditions and that are responsible for increasing its useful life and avoiding future problems. The maintenance factor, which includes checking the level and oil change of the front axle, is characterized as the most important analysis procedure.